Validation of the Portuguese Version of Impulsive–Premeditated Aggression Scale in an Inmate Population - Azevedo, Jacinto Costa; Pais-Ribeiro, José Luís; Coelho, Rui; Figueiredo-Braga, Margarida (Frontiers in Psychiatry, 2018)
Aggression is one of the core symptoms of antisocial personality disorder (ASPD) with therapeutic and prognostic relevance. ASPD is highly prevalent among inmates, being responsible for adverse events and elevated direct and indirect economic costs for the criminal justice system. The Impulsive/Premeditated Aggression Scale (IPAS) is a self-report instrument that characterises aggression as either predominately impulsive or premeditated. This study aims to determine the validity and reliability of the IPAS in a sample of Portuguese inmates. A total of 240 inmates were included in the study. A principal component factor analysis was performed so as to obtain the construct validity of the IPAS impulsive aggression (IA) and premeditated aggression (PM) sub-scales; internal consistency was determined by Cronbach’s alpha coefficient; convergent and divergent validity of the sub-scales were determined analysing correlations with the Barratt Impulsiveness scale, 11th version (BIS-11), and the Psychopathic Checklist Revised (PCL-R). The rotated matrix with two factors accounted for 49.9% of total variance. IA sub-scale had 11 items and PM sub-scale had 10 items. The IA and PM sub-scales had a good Cronbach’s alpha values: 0.89 and 0.88, respectively. The IA sub-scale is correlated with BIS-11 attentional, motor, and non-planning impulsiveness dimensions (p<0.05). The PM sub-scale is correlated with BIS-11 attentional, motor impulsiveness dimensions (p<0.05). The PM sub-scale is correlated with PCL-R interpersonal, lifestyle and antisocial dimensions (p<0.05). The IA sub-scale is not correlated with PCL-R. The Portuguese translated version of IPAS has adequate psychometric properties, allowing the measurement of impulsive and premeditated dimensions of aggression.